Novel Studies in the Designs of Natural, Synthetic, and Compound Hydrogels with Biomedical Applications - Cuéllar Gaona, Claudia Gabriela; Ibarra Alonso, María Cristina; Narro Céspedes, Rosa Idalia; Téllez Rosas, María Maura; Reyna Martínez, Ricardo; Luévanos Escareño, Miriam Paulina (Revista Mexicana de Ingenieria Biomedica, 2023)
Hydrogels are gaining widespread popularity in the biomedical field due to their extraordinary properties, such as biocompatibility, biodegradability, zero toxicity, easy processing, and similarity to physiological tissue. They have applications in controlled drug release, wound dressing, tissue engineering, and regenerative medicine. Among these applications, hydrogels as a controlled drug delivery system stands out, which releases active substances in precise amounts and at specific times. To explore the latest advances in the design of hydrogels, a literature review of articles published in indexed scientific journals, in Scopus and Science Direct, was carried out. This review aimed to discover and describe the most innovative hydrogel research with applications in the biomedical field; hydrogels synthesized with polymers of different origins were selected, such as; i. Natural (dextran, agarose, chitosan, etc.); ii. Synthetic (polyacrylamide, polyethylene glycol, polyvinyl alcohol, etc.); iii. Composites (interpenetrants, hybrid crosslinkers, nanocomposites, etc.). Comparative analysis revealed that hydrogels with composite materials show the most promise. These composite hydrogels combine the advantages of different polymers or incorporate additional components, offering enhanced properties and functionalities. In summary, hydrogels are versatile biomaterials with immense potential in biomedicine. Their unique properties make them suitable for diverse applications. However, innovative designs and formulations must continue to be explored to further advance the capabilities of hydrogels and expand their biomedical applications.